PANDU LOKASI WISATA KOTA TANGERANG DENGAN SISTEM INFORMASI GEOGRAFIS BERBASIS WEB - Sugeng Santoso; Ilamsyah Ilamsyah; Rio Abilaji (Jurnal Sistem Informasi dan Informatika (Simika), 2019)
Around the tourists who come to the city of Tangerang at this time makes the problem faced by the Tangerang Culture and Tourism Office. To help solve the problem faced, the author designed a web-based geographic information system (GIS) which would later help tourists in finding tourist locations in the city of Tangerang easily and precisely. The advantages of this web service can be used to solve the problems that exist in the Tangerang City Culture and Tourism Office and help tourists in obtaining tourist information, looking for attractions, displaying the path to the desired tourist attractions as well as providing photographs of interesting attractions. So that it can increase public interest or tourists who will visit to tour the city of Tangerang. The research methodology uses a prototyping approach and the system design uses UML (Unifed Modeling Language).